Students' expectations in an international Master of Science course in radiation biology. (1st February 2019) - Combs, Stephanie E.; Kessel, Carmen; Berberat, Pascal O.; Atkinson, Michael J.
Abstract: Purpose: We assessed students' expectations to a full two-year Master of Science course regarding workload, extracurricular activities, learning methods, and career plans. Materials and methods: A questionnaire was handed out to all students in the MSc radiation biology course. Questions evaluated the time for study and lectures expected a desire for specific teaching and testing formats, expectations from extracurricular activities as well as the motivation to study the subject and the future career plans. All students (100%) enrolled in the first semester were handed out and completed the questionnaire. Results: Most students had learned about the course from the internet (68.75%) or received information from teachers or professors (25%). Two students stated that all disciplines were equally relevant (25%). Others students made clear preferences: fourteen voted molecular biology (87.5%) as relevant, radiation protection in 93.75%, 81.25% consider physics the most important topic, followed by immunology (62.5%). Tutorials and lectures were preferred teaching formats. Generally, a workload of 20 hours per week is preferred. Conclusions: An ongoing feedback loop is important in designing a modern Master of Science course in the context of the Bologna process. Valuable information is given by students and should be integrated continuously in the design and continuation process.